2023
DOI: 10.5688/ajpe8874
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Pharmacy Student Stress During High-Stakes, Performance-Based Assessments in Skills-Based Courses

Abstract: To compare stress levels of pharmacy students in high-stakes, performance-based assessments (PBAs) administered during skills-based laboratory courses in normal classroom environments versus pandemic classroom environments impacted by COVID-19. Methods. In 2019, prior to the start of the COVID-19 pandemic, Doctor of Pharmacy (PharmD) student stress levels were assessed via a voluntary, paper-based survey before and after PBAs. Students were given a modified version of this survey in 2020 during the pandemic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For example, a survey study by Chaklader et al (n = 300 from 5 medical schools) found that students reported higher levels of depression and anxiety during the pandemic [65]. It is noteworthy that the one study which showed student stress levels were reduced during the pandemic reported hiring a wellness officer to integrate wellness activities into their curriculum [11]. The positive effects on student wellness reported in this study support this as an effective strategy for other colleges of pharmacy as well as other institutes of education to consider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a survey study by Chaklader et al (n = 300 from 5 medical schools) found that students reported higher levels of depression and anxiety during the pandemic [65]. It is noteworthy that the one study which showed student stress levels were reduced during the pandemic reported hiring a wellness officer to integrate wellness activities into their curriculum [11]. The positive effects on student wellness reported in this study support this as an effective strategy for other colleges of pharmacy as well as other institutes of education to consider.…”
Section: Discussionmentioning
confidence: 99%
“…While 13 of the 14 (92.3%) included studies reported some form of a negative impact of either COVID-19 or the adaptation of online learning such as increases in stress and anxiety levels, one study (0.07%) reported a decrease in student stress levels before exams. Specifically, Hettinger et al reported on the impact of COVID-19 on pharmacy student stress during high-stakes performance-based assessments before and during COVID-19 [11]. Based on data collected from responses from students at the Purdue University School of Pharmacy, stress levels before the performance-based exam fell from 3.78 to 3.45 when comparing pre-COVID-19 to during COVID-19, while stress levels similarly decreased from 2.84 to 2.52 after performance-based exams when comparing pre-COVID-19 to during COVID-19.…”
Section: Covid-19 Pandemic-driven Improvements and Innovations In Onl...mentioning
confidence: 99%
“… 8. , 9 , 10 In contrast, studies that surveyed pharmacy students were less conclusive 11 , 12 , 13 , 14 , 15 , 16. , 17 , 18 While some studies did align with the findings from medical or nursing students and noted an impact on student wellness, reported stress, and food or housing insecurity due to the pandemic, other studies found no significant differences in these reported factors.…”
Section: Introductionmentioning
confidence: 96%
“…The COVID-19 pandemic has negatively impacted all organizational constituents of pharmacy educational programs such as human, financial, intellectual, and knowledge capital. This has been amplified by decreased admission applications, financially strained operations, and burdened strategic plans [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. These challenges worsened faculty stress, tested resilience, and produced a level of lasting anxiety, all contributing to burnout and high levels of faculty turnover [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has been amplified by decreased admission applications, financially strained operations, and burdened strategic plans [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. These challenges worsened faculty stress, tested resilience, and produced a level of lasting anxiety, all contributing to burnout and high levels of faculty turnover [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%